Comparison of haemodynamic responses to direct laryngoscopy and intubation with gabapentin versus placebo - Peyyety Janaki Subhadra; G Nagaraj; M Hanumantha Rao (Journal of Clinical and Scientific Research, 2020)
Background: Laryngoscopy and tracheal intubation initiate tremendous changes in heart rate (HR) and blood pressure which could be associated with deleterious consequences in susceptible individuals. Methods: The effect of gabapentin on the haemodynamic responses to laryngoscopy and intubation in adults undergoing elective non-cardiac surgeries was investigated in the present study. Sixty adult patients of the American Society of Anaesthesiologists Grade I aged between 18–65 years and scheduled for different types of elective non-cardiac surgeries under general anaesthesia were randomly allocated to receive gabapentin 1200 mg or placebo capsules, at 6 h intervals starting the evening before surgery. After standard routine induction, succinylcholine was used to facilitate intubation. HR, systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial pressure (MAP) were recorded before and after the administration of the induction agent, immediately after laryngoscopy and intubation and at 1, 3, 5 and 10 min thereafter. Results: Patient characteristics were similar in both the groups. When compared to placebo group, Gabapentin group showed significantly lower HR (at post-induction, 0, 1 and 3 min; P < 0.05), SBP (at 0, 1 and 3 min; P < 0.05), DBP (at 0 and 1 min, P < 0.05) and MAP (at 0, 1 and 3 min, P = 0.05) after laryngoscopy and intubation. Conclusions: Gabapentin, under the present study design, attenuated the pressor response to laryngoscopy and intubation in terms of HR, SBP, DBP and MAP in patients undergoing elective non-cardiac surgeries.